Effects of auricular acupoint pressing combined with continuous scenario simulation nursing interventions for patients with Meniere's disease (耳穴压丸联合持续性情景模拟护理干预耳眩晕患者效果观察) - TIAN Yuan (田媛); QI Shasha (齐莎莎); HU Jingyi (胡静怡); LI Mengting (李梦婷); ZHANG Jingran (张京然); GENG Qingwen (耿庆文); ZHANG Ying (张莹) (Association of Integrative Nursing, 2024)
Objective To investigate the clinical effect of auricular acupoint pressing combined with continuous scenario simulation nursing interventions for patients with Meniere's disease. Methods A total of 60 patients who met the inclusion and exclusion criteria were randomly divided into the observation group and control group using a random number table, with 30 patients in each group. The control group received routine treatment and nursing, while the treatment group received combined with continuous scenario simulation. The intervention efficacy, patient satisfaction and sleep quality were measured and compared between groups. Results The total effective rate of intervention was 80. 00%(24/30) in the observation group and 63. 33%(19/30) in the control group, with a significant difference(P＜0. 05). The nursing satisfaction rate in the observation group was higher than that in the control group (96. 67% vs. 66. 67%), with a significant difference (P＜0. 05). The Pittsburgh Sleep Quality Index (PSQI) score in the observation group was lower than that in the control group (P＜0. 05). Conclusion The application of auricular acupoint pressing combined with continuous scenario simulation nursing interventions can improve sleep quality and nursing satisfaction of patients with Meniere's disease . (目的 探讨耳穴压丸联合持续性情景模拟护理干预耳眩晕患者的效果。方法 60例耳眩晕患者随机分为观察组和对照组, 各30例。对照组给予常规干预, 观察组在对照组基础上应用耳穴压丸联合持续性情景模拟护理干预。评估两组临床疗效、护理满意度和睡眠质量。结果 观察组总有效率为80. 00%(24/30)、护理满意度96. 67%(29/30), 高于对照组的63. 33%(19/30)和66. 67%(20/30), 差异具有统计学意义(P＜0. 05)。观察组匹兹堡睡眠质量指数量表(PSQI)评分低于对照组, 差异有统计学意义(P＜0. 05)。结论 耳穴压丸联合持续性情景模拟护理干预可改善耳眩晕患者睡眠质量, 提高患者满意度。)